2019
DOI: 10.1093/molbev/msz005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of Arabian Peninsula Populations: Shedding Light on the History of a Fundamental Bridge between Continents

Abstract: The Arabian Peninsula (AP) was an important crossroad between Africa, Asia, and Europe, being the cradle of the structure defining these main human population groups, and a continuing path for their admixture. The screening of 741,000 variants in 420 Arabians and 80 Iranians allowed us to quantify the dominant sub-Saharan African admixture in the west of the peninsula, whereas South Asian and Levantine/European influence was stronger in the east, leading to a rift between western and eastern sides of the Penin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 80 publications
7
79
2
Order By: Relevance
“…In addition, it is evident, in conjunction with 70 African mitogenomes, that the sub-haplogroup L3x1b clusters with an Ethiopian sample confirming the ancient step out in the region out of African. Furthermore, we observe admixture among geographical regions in the UAE, which is also observed in previous studies [ 12 , 60 ]; Figure 3 B depicts admixture results where a clear admixture event at K = 7 number ancestral population can be seen. The lack of population structure is also addressed using a DAPC analysis ( Figure 3 C), which demonstrate non-clustering of different cities and geographical regions.…”
Section: Resultssupporting
confidence: 88%
“…In addition, it is evident, in conjunction with 70 African mitogenomes, that the sub-haplogroup L3x1b clusters with an Ethiopian sample confirming the ancient step out in the region out of African. Furthermore, we observe admixture among geographical regions in the UAE, which is also observed in previous studies [ 12 , 60 ]; Figure 3 B depicts admixture results where a clear admixture event at K = 7 number ancestral population can be seen. The lack of population structure is also addressed using a DAPC analysis ( Figure 3 C), which demonstrate non-clustering of different cities and geographical regions.…”
Section: Resultssupporting
confidence: 88%
“…The African influence has also extended into presentday India, as evidenced by a study that describes a population in the western part of India that has been substantially influenced by African populations, specifically Bantu-speakers (Narang et al, 2011). Similarly, a recent study (Fernandes et al, 2019) has shown a dominance of sub-Saharan African admixture in the west of the Arabian Peninsula, whereas South Asian and Levantine/European influence was stronger in the east.…”
Section: Introductionmentioning
confidence: 96%
“…Studies on modern Bedouins elsewhere, e.g. in Qatar report them as 'coldspots' of admixture in the Peninsula compared to other populations 45 . It is suggested that the Negev Bedouins originate from a small founder population and most of their ancestors migrated from the Arabian Peninsula to the Negev and Sinai regions around 700 CE, i.e., shortly after the spread of Islam 46 .…”
Section: Discussionmentioning
confidence: 99%